Globalisasi dan Diaspora Cina dalam Perspektif Post-Kolonial: Dinamika Strategi Ekonomi dan Identitas Budaya - Arie Setyaningrum (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
This article attempts to draw the effect of globalization shown through the success of Chinese Diaspora in pursuing global capitalism across national and cultural borders which in turn enriched cultural values and class strategy. The countercultural-production of diasporan Chinese is a complex dynamic process rooted in the history of diasporan and European colonialism. In regard to this phenomenon, this article focuses on several issues of how globalization provides opportunities for establishing capital networks despite sociopolitical obstacles in the host count-ries. To some extent, the effect of globalization will also generate hybrid culture between the sense of being Chinese and adopted local identities.